Determinación de la calidad del agua de riego en la captación y distribución para la parroquia Belisario Quevedo, provincia de Cotopaxi, periodo 2015 - Ponce Rosero, Henry German (2016)
In the investigation the principal objective was the determination of the quality of water irrigation and distribution to propose mitigation measure of Belisario Quevedo Parish, of Cotopaxi¨s province. It has founded in August 6th 1936. It has 6359 inhabitants; about 1250 are users of the system which is the principal supplying of Illuchi river.” SENAGUA” is the management that organize the irrigation, in the process 1636 of Illuchi river with a concession of 543L/S. The physic-chemical of water results to determinate the quality in boro ammonia nitrogen and potential hydrogen are inside limits in the three monitoring points of view. The bicarbonates are inside of the parameters in the first point with 4.32 mg/l .Also we have seen the last two and three points begin decrease the bicarbonates value. It has 1.5 to 8.5 mg/l as a limit....